The Carved Brush : Seal Carving, Calligraphy, and Painting by Qi Baishi (1863-1957) - Tsao, Jung Ying; Yee, Craig L.; Erickson, Britta (Book collections on Project MUSE., 2014)
Born into a poor farming family and coming of age during China's century of civil strife, Qi Baishi transformed the elite brush art of China's literati scholars into a universal art form appreciated by people of all social backgrounds. His distinctly modern art language breaks through class and cultural barriers through use of expressive "carved" brushwork, juxtaposition of vibrant colours against deep and rich ink tones, poetic economy in form and composition, and choice of emotionally resonant subject matter. For these reasons, Qi Baishi's art is the ideal gateway through which art lovers of any class or culture can learn about the millenia-old tradition of Chinese brush painting. A selection of Qi Baishi's seal carving - the art of the "iron brush"--Links his origins as an artisan carver to his life as China's most celebrated calligrapher, poet and painter. The scholarly discipline calligraphy then forms the basis for our understanding Qi Baishi's distinctive carved brushwork. Published in association with Marquand Books and the Mozhai Foundation.